Hydrogen isotopic compositions of long-chain alkenones record freshwater flooding of the Eastern Mediterranean at the onset of sapropel deposition - van der Meer, Marcel T.J.; Baas, Marianne; Rijpstra, W. Irene C.; Marino, Gianluca; Rohling, Eelco J.; Sinninghe Damsté, Jaap S.; Schouten, Stefan (Earth and planetary science letters, 2007)
Sapropels are organic-rich sediment layers that were intermittently deposited in the Mediterranean Sea, especially in its eastern basin, during the last 10Myr. The associated anoxic events that gave rise to sapropel formation resulted indirectly from the impact of African monsoon maxima on the basin's hydrography. Sharp shifts in oxygen isotopes ( δ 18O) to values more depleted in the heavy isotope ( 18O) in carbonates from surface dwelling planktonic foraminifera, slightly preceding sapropel deposition, suggest that the Mediterranean was flooded by large amounts of freshwater leading to the development of a low salinity of the surface water and a strong density stratification of the water column. However, the degree of freshwater flooding and concomitant drop in sea surface salinity (SSS) remain elusive. Recent work has shown that the hydrogen isotope ( δD) values of long-chain alkenones produced by haptophyte algae depend mainly on the δD of the water and on salinity, and may therefore offer a new tool for salinity reconstructions. Our analysis of the δD of alkenones from last interglacial sapropel S5 from the Aegean Sea shows a large decrease in δD of 25‰ at the onset of sapropel formation, suggesting a drop in SSS of 6, from 39 to 33. Although the absolute SSS estimates should be interpreted with care as they are subject to relatively large uncertainties, the estimated SSS values appear quite reasonable as they, for example, yield SSS before sapropel deposition similar to that of the present day Aegean Sea. To reduce uncertainties in SSS estimates, the δD-salinity relationship has to be better constrained with cultures and also tested in field studies. However, our results do illustrate the promise of a combined use of δD of alkenones, U 37 k′ of alkenones, and δ 18O of surface dwelling planktonic foraminifera, for SSS reconstructions.